Risk Management VoltWave Networks eV-Station (Electric Vehicle Charging Station) - Kurniawan, Kurniawan; Indradewa, Rhian; Iskandar, Muhammad Dhafi; Negoro, Dimas Angga (Syntax Literate, 2025)
The development of electric vehicle (EV) technology has led to an increase in the need for supporting infrastructure such as Electric Vehicle Charging Stations (EVCS). However, these service providers face various risks, both internal and external, that can hinder the achievement of business goals. This study aims to analyze and design risk management strategies in VoltWave eV-Station in order to anticipate and minimize potential losses. This research uses a qualitative method with a case study approach that focuses on risk management design based on the ISO 31000:2018 framework. Data was obtained through observations, interviews, and internal company documentation. The results of the study show that the main risks faced include market uncertainty, regulatory changes, operational disruptions, and human resource factors. The proposed risk mitigation strategy includes the preparation of SOPs, employee training, service innovation, product diversification, and continuous evaluation. The implications of this study provide practical guidance for startups in the electric vehicle sector in building a risk management system that is adaptive, sustainable, and supports long-term business growth.